2004
DOI: 10.1161/01.str.0000143153.76460.7d
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Augmented Exercise Therapy Time After Stroke

Abstract: Background and Purpose-To present a systematic review of studies that addresses the effects of intensity of augmented exercise therapy time (AETT) on activities of daily living (ADL), walking, and dexterity in patients with stroke. Summary of Review-A database of articles published from 1966 to November 2003 was compiled from MEDLINE, CINAHL, Cochrane Central Register of Controlled Trials, PEDro, DARE, and PiCarta using combinations of the following key words: stroke, cerebrovascular disorders, physical therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
630
4
37

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 968 publications
(708 citation statements)
references
References 51 publications
19
630
4
37
Order By: Relevance
“…This finding is reflective of a recent systematic review which also identified stroke survivors to be physically active for on average 60% of their physiotherapy sessions 12 . It is important to note that as the sessions in this study consisted solely of completing the GRASP exercises, and did not include other activities (e.g.…”
Section: Timementioning
confidence: 52%
See 3 more Smart Citations
“…This finding is reflective of a recent systematic review which also identified stroke survivors to be physically active for on average 60% of their physiotherapy sessions 12 . It is important to note that as the sessions in this study consisted solely of completing the GRASP exercises, and did not include other activities (e.g.…”
Section: Timementioning
confidence: 52%
“…Time continues to remain the dominant measure of intensity both in research 7,12 and in clinical guidelines 13,14 . It is the measure used to synthesize data in meta-analyses 3,12,15 and is the standard by which clinicians and services are evaluated 16 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The classical funnel plot of the metaanalysis is therefore ordered by increment of the variable studied, for instance chronologically by date of publication as in the seminal report by Lau et al (1992), or by duration of exercise therapy as in the article by Kwakkel et al (2004). The interest of a cumulative meta-analysis ordered by date of publication, as indicated by the authors, is that it may show the time at which sufficient evidence of the superiority of one treatment over another has accumulated.…”
mentioning
confidence: 99%